Insertions/Deletions in the Antithrombin Gene: 3 Mutations Associated with Non-Expression - Daly, Martina; Perry, David J; Harper, Paul L; Daly, Helena M; Roques, Antoine W W; Carrell, Robin W (Thrombosis and Haemostasis, 1992)
We have investigated the molecular basis of antithrombin deficiency in 3 individuals, 2 of whom had a proven family history of thromboembolic disease. An approximate 50% reduction in functional and immunologic levels of antithrombin was detected in plasma from the propositi indicating an allelic deficiency of antithrombin. In each case direct sequencing of amplified DNA revealed a novel mutation involving single bases: two being insertions, of a T in codon 48 and an A in codon 208, and the third being the deletion of an A in codon 370. The three mutations, which were confirmed by cloning and sequencing the normal and variant alleles, all caused frameshifts leading to premature termination of protein translation. In no case could a truncated antithrombin be detected in plasma from the propositus suggesting either that it fails to be secreted, or is rapidly degraded.